Uji Aktivitas Antibakteri Ekstrak Daun Gelinggang (Cassia alata L): Antibacterial Activity Test of Gelinggang Leaf Extracts (Cassia alata L) - Khofifah Nur Oktavia; Fika Aryati; Herman Herman (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2021)
Traditionally, gelinggang leaves are widely used for treatment of various skin diseases. The potential of gelinggang leaves as a medicinal plant is expected due to the presence of secondary metabolite compounds that have activities, one of which can inhibit the growth of fungi and bacteria. This study aims to determine the antibacterial activity of gelinggang leaf extract against Staphylococcus aureus and Escherichia coli bacteria. The study began with extraction process of gelinggang leaves, phytochemical screening tests and testing of antibacterial activity from gelinggang leaf extracts carried out by the agar diffusion method using a well. Gelinggang leaf samples were macerated with 96% ethanol solvent and then tested for antibacterial activity in concentrations of 5%, 10%, and 15%. The results of the phytochemical screening test indicated that the gelinggang leaf extract was positive for flavonoids, saponins, phenolics, and terpenoids. On antibacterial activity test of the ethanolic extract of gelinggang leaves, it revealed that there was an inhibition activity for both Staphylococcus aureus and Escherichia coli bacteria with the best activity at a concentration of 15%.